Fellow-Feeling end the Moral Life - Filonow, Joseph D (Cambridge University Press, 2013)
How do our feelings for others shape our attitudes and conduct towards them? Is morality primarily a matter of rational choice, or instinctual feeling? Joseph Duke Filonowicz takes the reader on an engaging, informative tour of some of the main issues in philosophical ethics, explaining and defending the ideas of the earlymodern British sentimentalists. These philosophers – Shaftesbury, Hutcheson, Hume, and Smith – argued that it is our feelings, and not our “reason,” which ultimately determine how we judge what is good or bad, right or wrong, and how we choose to act towards our fellow human beings. Filonowicz draws on contemporary sociology and evolutionary biology as well as present-day moral theory to examine and defend the sentimentalist view and to challenge the rationalistic character of contemporary ethics. His book will appeal to readers interested in both history of philosophy and current ethical debates.